Heterogeneity of rhythmic suprachiasmatic nucleus neurons: Implications for circadian waveform and photoperiodic encoding - Schaap, Jeroen (National Academy of Sciences, 2003)
Circadian rhythms in neuronal ensemble, subpopulations, and single unit activity were recorded in the suprachiasmatic nuclei (SCN) of rat hypothalamic slices. Decomposition of the ensemble pattern revealed that neuronal subpopulations and single units within the SCN show surprisingly short periods of enhanced electrical activity of ≈5 h and show maximal activity at different phases of the circadian cycle. The summed activity accounts for the neuronal ensemble pattern of the SCN, indicating that circadian waveform of electrical activity is a composed tissue property. The recorded single unit activity pattern was used to simulate the responsiveness of SCN neurons to different photoperiods. We inferred predictions on changes in peak width, amplitude, and peak time in the multiunit activity pattern and confirmed these predictions with hypothalamic slices from animals that had been kept in a short or long photoperiod. We propose that the animals' ability to code for day length derives from plasticity in the neuronal network of oscillating SCN neurons.